ANALISA HASIL PENGELASAN KAKI PULSATOR PENGGERAK JIG YUBA KK SINGKEP UNTUK MENDAPATKAN KEKUATAN KONSTRUKSI OPTIMA - Rodiawan, Rodiawan; Suhdi, Suhdi S.S.T., M.T (Mesin, 2016)
Pulsator is one tool driving jig used PT. Timah Tbk in the process of separation of tin ores and minerals Downstream based differences in specific gravity (SG). Damage that occurs in the pulsator especially in the legs, can be caused by high vibration caused jig continuously during operation so as to make the bolt fastener will eventually become worn. Process improvements made PT. Timah (Persero) Tbk to damage pulsator foot is by means of welding, the connecting leg pulsator damaged (broken) with cast or plate material. Given the importance of the pulsator for tin ore separation process, we conducted a study of the results of the pulsator legs welded using electrodes AWS A5.15 cin-1, cin-cin-2 and 3 used PT. Timah (Persero) Tbk. The aim of this study is to find the right electrode is used for welding process that results weld toe pulsator can provide optimum strength welded construction. The research method is by way of experiment by comparing the electrode cin-1, cin-2 and cin-3 brand Nikko Steel against the welding process using the foot pulsator pulsator and plate material as the connection. After welding is done then analyze the results of the pulsator weld toe with the review of test results toughness, hardness and microstructure of welds. The test results obtained material cin-3 has a value of hardness and toughness that is higher than the material cin-1 and cin-2, with a value of 109 HRBÂ hardness and toughness value of 6.53 joules/mmÂ². The high hardness and toughtness of cin-3 compared with cin1 and cin-2 when showed from the microstructure of the material is cin-3 contained a very hard.Key words : Pulsator, cast iron, welding, Elektrode AWS A5.15